Islamic Populism in Palembang in the 1950s - Viana, Ryllian Chandra Eka (Muslim Politics Review, 2022)
This study discusses the emergence of Islamic populism in Palembang in the 1950s. In the official narratives of Indonesian history, the political turbulence in Palembang that occurred in the mid-1950s is often associated with a regional Army commander-led rebellion. This research instead finds that Islamic groups played a crucial role in developing the preliminary conditions before the military group took the initiative to pull the trigger. Islamic groups, through their network of ulama, tried to unite all groups opposed to Jakarta’s leadership and communism to incorporate under one umbrella of political identity: Islam. We determine that the emergence of Islamic populism in Palembang was caused by multiple grievances: economic decline, redistribution of welfare to the region, the exclusion of Islamic groups, and the fear of communism. However, Islamic populism only succeeded in uniting factions in the Islamic community but failed to reach other groups because of the social cleavages from previous feuds.